Placental Growth Factor Triggers Epithelial‐to‐Mesenchymal Transition‐like Changes in Rat Type II Alveolar Epithelial Cells: Activation of Nuclear Factor κB Signalling Pathway. Issue 5 (8th June 2016) - Zhang, Liang; Zhao, Shuang; Yuan, Lijie; Wu, Hongmin; Jiang, Hong; Luo, Gang
Abstract: Epithelial‐to‐mesenchymal transition (EMT) occurs frequently in lung epithelium in response to damage stimuli, such as inflammation and oxidative stress. Our group has already found an excessive release of placental growth factor (PLGF) in hyperoxic lung injury in newborn rodents. Nonetheless, whether this increased PLGF plays a role in mediating EMT process of alveolar epithelial cells (AECs) is unclear and requires further investigation. In this study, primary type II AECs were first isolated for neonatal Sprague Dawley (SD) rats and treated with different doses (25 or 100 ng/ml) of recombinant PLGF for 48 hr. As compared to the untreated AECs, exogenous PLGF induced a reduction in E‐cadherin (a critical epithelial maker) and increases in vimentin and fibronectin (mesenchymal markers) in a dose‐dependent manner. The higher dose was more potent in promoting the EMT‐like changes in AECs. We also found that PLGF promoted the degradation of nuclear factor κB (NFκB) inhibitor (IκBα), induced phosphorylation of NFκB p65 at Ser 536 and enhanced p65 nuclear translocation in primary AECs. In addition, the NFκB inhibitor BAY 11‐7082 partly counteracted PLGF‐induced alterations in EMT‐related proteins in rat AECs. In summary, our study demonstrates that exogenous PLGF can induce EMT‐like changes in type II AECs at least partly by activating NFκB signalling transduction in vitro . PLGF may play a role in driving fibrotic lesions and thus can be a promising target for lung diseases.